2012
DOI: 10.1002/jcp.24132
|View full text |Cite
|
Sign up to set email alerts
|

Altered expression and signal transduction of endothelin‐1 receptors in heritable and idiopathic pulmonary arterial hypertension

Abstract: Human pulmonary arterial smooth muscle cells (PASMC) were isolated from elastic pulmonary arteries dissected from lungs of individuals with and without pulmonary arterial hypertension (PAH). Reflecting increased smooth muscle constriction in cells from PAH subject, Ca 2+ influx in response to endothelin-1 (ET-1) increased in all the PAH PASMC populations relative to the normal donor control cells. The ETA receptor mRNA levels remained unchanged, whereas the ETB receptor mRNA levels decreased in both heritable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 22 publications
(30 reference statements)
0
34
0
Order By: Relevance
“…1A). PASMCs express ETA, 30,32 and ETA was upregulated in PAH lungs compared with controls and further overexpressed in SCD (Fig. 1A).…”
Section: Scd Lungs Have Increased Expression Of Pah-promoting Signal mentioning
confidence: 94%
“…1A). PASMCs express ETA, 30,32 and ETA was upregulated in PAH lungs compared with controls and further overexpressed in SCD (Fig. 1A).…”
Section: Scd Lungs Have Increased Expression Of Pah-promoting Signal mentioning
confidence: 94%
“…ET-1 has been implicated as an important factor in the development of PH. Its circulating level is increased, its receptor density in PA is upregulated and vasoconstrictory effect is enhanced during PH; and antagonists of ET-receptors can effectively prevent and reverse PH [60,61,62,63,64,65,66]. Enhanced SOCE has been reported in many different models of experimental PH, including CHPH [34,67], monocrotaline-induced PH [36] and cigarette smoke-induced PH [68], and in patients of idiopathic pulmonary arterial hypertension (IPAH)[69,70,71].…”
Section: Discussionmentioning
confidence: 99%
“…Increased plasma levels of ET-1 of systemic (rather than of pulmonary) origin, are detected in patients with several forms of PAH [19]. Recent studies have confirmed the hypothesis of a prominent role played by ET-1 in PAH [20][21][22]. Converging experimental evidence has shown ET-1 activation in the lungs, leading to vasoconstriction and remodelling of the pulmonary microcirculation [5] ( Fig.…”
Section: The Endothelin Pathway In Pulmonary Arterial Hypertensionmentioning
confidence: 83%